Perbandingan Kemampuan Pemecahan Masalah Matematis Siswa Antara Pembelajaran yang Menggunakan Model Team Assisted Individualization Dengan Model Direct Instruction - Muh. Aripin Nurmantoro (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2019)
This purpose of this study are to find out to determine the mathematical problem solving abilities of students using the Team Asissted Individualization learning models; mathematical problem solving abilities of students who use the Direct Instruction learning models; and to find out the better mathematical problem solving abilities of students who use the Team Asissted Individualization learning models with Direct Instruction. This research was conducted by experimental method, using cluster random sampling technique, and after drawing, Class VIII B and Class VIII D were selected as samples. Class VIII D was used as the experimental class I, where the learning used the Learning Team Team Individualization model and class VIII D was used as the experimental class II, where the learning used the Direct Instruction learning model. While the data analysis technique used in this study is the t-test. Based on the results of data analysis that has been done, it can be concluded that the mathematical problem solving abilities of students who use The Team Asissted Individualization learning models are better than Direct Instruction Model.